ATTITUDES OF VIETNAMESE CONFUCIANS TOWARD BUDDHISM: A SURVEY OF BUDDHIST EPITAPHS IN THE LE AND NGUYEN DYNASTIES - Le, Sy Dong (Trường Đại học Đà Lạt, 2024)
Buddhism is one of the major religions practiced in Vietnam. The attitude of the Vietnamese toward Buddhism during different periods is therefore an important topic. In this article, we analyze 145 Buddhist epitaphs from the Le and Nguyen dynasties. Our aim is to gain insight into three aspects of the attitude of Confucians toward Buddhism: The extent of Confucian involvement in the creation of Buddhist epitaphs, the level of sympathy expressed toward Buddhism by Confucians, and the expression of Buddhist thought in the spiritual life of the Vietnamese, as revealed by the inscriptions. We thereby aim to provide a more comprehensive understanding of how Buddhism has impacted Vietnamese spirituality.